IMPLEMENTASI ASAS KEADILAN PADA PERATURAN PERUNDANGAN-UNDANGAN DI INDONESIA TERHADAP PERKEMBANGAN TEKNOLOGI DI ERA GLOBALISASI - Yeremia Zebua; Priyanka Fretiyanti Tirsa Sianressy (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2026)
Technological disruption in the era of globalization presents significant challenges for the legal system in ensuring digital justice, particularly regarding privacy protection, digital rights, cybercrime, and the gap in access to technology (Hukum et al. 2024). The rapid development of the internet, social media, artificial intelligence, and electronic information systems has transformed various aspects of Indonesian society, including legal, political, economic, and social aspects, thus demanding regulations that are adaptive, responsive, and oriented towards the principles of democracy and justice. This study aims to analyze the state's legal regulations regarding these technological dynamics and evaluate the extent to which the principles of democracy and justice have been fulfilled in handling technology abuse in Indonesia. The method used is normative legal research with a statutory and conceptual approach. The results of the study indicate that technological regulations have been accommodated through Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016 concerning Amendments to the ITE Law, and strengthened by Law Number 27 of 2022 concerning Personal Data Protection. However, its implementation still faces various problems, such as multiple interpretations of norms, potential criminalization, and suboptimal protection of human rights. Therefore, it is necessary to strengthen legal policies that can guarantee legal certainty, protect citizens' rights, and maintain a balance between freedom of expression and legal responsibility in the digital space.